Transnational collective actions for cross-border data protection violations - Federica Casarosa (Internet Policy Review, 2020)
With the Cambridge Analytica/Facebook scandal, online surveillance clearly showed its negative effects. However, few individuals were able to recover any damages from the data protection violation that occurred. The EU General Data Protection Regulation contains legal tools to coordinate the interests of data subjects together in the case of infringements that occur across member states of the European Union, not only at the national level (Article 80), but potentially at the transnational level, as implied by Article 81. However, only a reform addressing the rules applicable to the standing of associations and non-governmental organisations in transnational claims as well as those concerning jurisdiction and international lis pendens would allow EU citizens to take full advantage of this opportunity.